Paper Puppets as an Interactive Learning Medium in Third Grade Elementary Schools - Prasetya, Anindhitya Yudhanta; Sukasih, Sri (Universitas Pendidikan Ganesha, 2024)
In the current era of globalization, educational challenges are becoming increasingly complex and require innovation in the learning process to improve the quality of student learning outcomes. One innovation that is currently developing rapidly is the application of learning media. The problem found by researchers in the field is the lack of application of the learning media used which affects student learning outcomes. The purpose of this research is to analyze the influence of paper puppet learning media has on the third grade elementary school level. The type of research used is quantitative research with a pre-experimental designs research design with pretest-posttest control group design. The subjects of this research were third grade elementary school students at elementary school with a sample of 53 students and the sampling technique used was random sampling. The data collection techniques used were interviews, questionnaires, and tests. Data analysis techniques used are descriptive analysis and inferential analysis. The research results obtained were that there was an influence on student learning outcomes after testing and comparing the application of paper puppet media. The conclusion of the research obtained were that there was an influence on student learning outcomes between before and after implementing paper puppet learning media.